2006
DOI: 10.1080/07373930600778221
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for Accurate CFD Modeling of Spray-Drying Process

Abstract: The paper presents concluding results of extensive experimental and theoretical research on confident CFD modeling of spray drying. An earlier developed experimental method to determine spray-drying kinetics in a lab scale allowed us to find a critical material moisture content and to determine generalized spray-drying curves. The generalized drying curves, identical in shape in the laboratory and pilot plant units, were used in the CFD model of spray drying process. Extensive simulations for spray drying of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…is not using experimental data/measurements; it is through an overall transfer equation for the heat loss with the ambient (Julklang and Golman, 2015). Respect to M C sensitivity, the results obtained in this paper are in agreement with the outcomes showed by Zbiciński and Li (2006). They found a relation between the critical moisture content with the average drying rate of a maltodextrin spray drying system.…”
Section: Modelling a Production Scale Milk Drying Process: Parameter supporting
confidence: 94%
“…is not using experimental data/measurements; it is through an overall transfer equation for the heat loss with the ambient (Julklang and Golman, 2015). Respect to M C sensitivity, the results obtained in this paper are in agreement with the outcomes showed by Zbiciński and Li (2006). They found a relation between the critical moisture content with the average drying rate of a maltodextrin spray drying system.…”
Section: Modelling a Production Scale Milk Drying Process: Parameter supporting
confidence: 94%
“…Several publications have comprehensively reported how 2-D and 3-D simulation approaches using various CFD packages (e.g. Fluent and CFX) can be helpful to predict agglomeration behavior during spray drying [33,49,97], evaluate particle trajectories [11], design new drying chamber configurations and assess atomizer performance [11,[36][37][38] as well as to study gas distribution within drying chambers [11,28,33,34,45,50,53,68,93,101,111]. The accuracy of prediction by finerscale approaches mainly depends on the selection of mass-heat-momentum conservation equations, the accuracy of turbulence models, the appropriateness of numerical methods used for solving equations and the quality of grid generation and algorithm development [28,47,50].…”
Section: "2-d" and "3-d" (Finest-scale) Simulation Approachesmentioning
confidence: 99%
“…It is difficult to closely match the model and experimental data in pilot-scale spray dryer modeling where there are significant uncertainties present in the measurement data in combination with the non-linearities and assumptions influencing accurate modeling of the spray drying process. The discrepancies between model predictions and experimental data, nevertheless, fall within an acceptable range of previously reported literature over the modeling of spray drying processes [53,123,126,127,[204][205][206]. Therefore, it could be concluded that, in general, the airflow temperature patterns followed the experimental trends, capturing the characteristics of the airflow (rotating and non-rotating streams).…”
Section: Model Validationsupporting
confidence: 79%